2003
DOI: 10.1097/00006223-200311000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The End-of-Life Nursing Education Consortium (ELNEC) Experience

Abstract: The End-of-Life Nursing Education Consortium (ELNEC) is a train-the-trainer educational program to help nursing faculty integrate care of the dying patient and the patient's family in the nursing curriculum. The authors describe the ELNEC experience, which prepares nurse educators to competently teach end-of-life care, and provides them with the necessary knowledge, skills, and resources to effectively integrate end-of-life content into existing nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…These targeted curricula could be taught to practicing nurses within the context of the setting and the patient population they serve. 17 For example, nurses practicing in outpatient settings were more likely to rate ''telling patients how their illness may impact their life'' as an extremely important and under-utilized skill. An appropriate intervention may assist nurses working in out-patient settings to address aspects of care that allow patients to preserve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These targeted curricula could be taught to practicing nurses within the context of the setting and the patient population they serve. 17 For example, nurses practicing in outpatient settings were more likely to rate ''telling patients how their illness may impact their life'' as an extremely important and under-utilized skill. An appropriate intervention may assist nurses working in out-patient settings to address aspects of care that allow patients to preserve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…21 While these findings suggest nurses view patient discussions of hospice and prognosis as outside their scope of practice, other studies suggest nurses desire more involvement when these aspects of communication are necessary for advance care planning and coordination of care. 17,22,23 Families also identify the important role nurses play in communication. In a community-based study, families reported that nurses were more likely to have discussed symptoms and their treatment than physicians and that discussions with nurses were more understandable than those with physicians.…”
Section: Discussionmentioning
confidence: 99%
“…In examining end of life care and education for nurses over the past 20 years, researchers (Matza et al 2003;Mallory 2003) have systematically cited differences.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequately trained nurses practicing WDLS could result in substandard care for patients and families in the ICU setting and could contribute to increased emotional strain for nurses. [20][21][22][23] Given their role in withdrawal practices and the numbers of patients who experience WDLS, formal training should be included in curricula for basic nursing education. Institutions should also include formal training about WDLS during nurses' orientation for critical care.…”
Section: Discussionmentioning
confidence: 99%